Enteric hyperoxaluria in chronic pancreatitis. Issue 19 (May 2017) - Demoulin, Nathalie; Issa, Zaina; Crott, Ralph; Morelle, Johann; Danse, Etienne; Wallemacq, Pierre; Jadoul, Michel; Deprez, Pierre H.
Abstract : Abstract: Chronic pancreatitis may lead to steatorrhea, enteric hyperoxaluria, and kidney damage. However, the prevalence and determinants of hyperoxaluria in chronic pancreatitis patients as well as its association with renal function decline have not been investigated. We performed an observational study. Urine oxalate to creatinine ratio was assessed on 2 independent random urine samples in consecutive adult patients with chronic pancreatitis followed at the outpatient clinic from March 1 to October 31, 2012. Baseline characteristics and annual estimated glomerular filtration rate (eGFR) change during follow-up were compared between patients with hyper- and normo-oxaluria. A total of 48 patients with chronic pancreatitis were included. The etiology of the disease was toxic (52%), idiopathic (27%), obstructive (11%), autoimmune (6%), or genetic (4%). Hyperoxaluria (defined as urine oxalate to creatinine ratio >32 mg/g) was found in 23% of patients. Multivariate regression analysis identified clinical steatorrhea, high fecal acid steatocrit, and pancreatic atrophy as independent predictors of hyperoxaluria. Taken together, a combination of clinical steatorrhea, steatocrit level >31%, and pancreatic atrophy was associated with a positive predictive value of 100% for hyperoxaluria. On the contrary, none of the patients with a fecal elastase-1 level >100 μg/g had hyperoxaluria. Longitudinal evolution of eGFR was available in 71% of the patients, with a mean follow-up of 904 days. After adjustment for established determinants of renal function decline (gender, diabetes, bicarbonate level, baseline eGFR, and proteinuria), a urine oxalate to creatinine ratio >32 mg/g was associated with a higher risk of eGFR decline. Hyperoxaluria is highly prevalent in patients with chronic pancreatitis and associated with faster decline in renal function. A high urine oxalate to creatinine ratio in patients with chronic pancreatitis is best predicted by clinical steatorrhea, a high acid steatocrit, and pancreatic atrophy. Further studies will need to investigate the mechanisms of renal damage in chronic pancreatitis and the potential benefits of therapies reducing oxaluria.